Numbers count: How STIM and Orai stoichiometry affect store-operated calcium entry. (May 2019) - Yen, Michelle; Lewis, Richard S.
Graphical abstract: Highlights: The ER Ca 2+ sensor STIM1 is a dimer, and Ca 2+ release initiates activation by triggering association of its luminal domains. The CRAC channel is structurally and functionally a hexamer of Orai1 subunits. STIM1 binds to all six Orai1 subunits to effectively activate the CRAC channel and confer its signature pore properties. Current models propose STIM1 binding to individual or paired Orai1 C-termini. Abstract: Substantial progress has been made in the past several years in establishing the stoichiometries of STIM and Orai proteins and understanding their influence on store-operated calcium entry. Depletion of ER Ca 2+ triggers STIM1 to accumulate at ER-plasma membrane junctions where it binds and opens Ca 2+ release-activated Ca 2+ (CRAC) channels. STIM1 is a dimer, and release of Ca 2+ from its two luminal domains is reported to promote their association as well as drive formation of higher-order STIM1 oligomers. The CRAC channel, originally thought to be tetrameric, is now considered to be a hexamer of Orai1 subunits based on crystallographic and electrophysiological studies. STIM1 binding activates CRAC channels in a highly nonlinear way, such that all six Orai1 binding sites must be occupied to account for the activation and signature properties of native channels. The structural basis of STIM1 engagement with the channel is currently unclear, with evidence suggesting that STIM1 dimers bind to individual or pairs of Orai1 subunits. This review examines evidence that has led to points of consensus and debate about STIM1 and Orai1 stoichiometries, and explains the importance of STIM-Orai complex stoichiometry for the regulation of store-operated calcium entry.